Nanobody-photosensitizer conjugates for the treatment of epithelial ovarian cancer through targeted photodynamic therapy - Wübbeke, Lina (Student Undergraduate Research E-journal!, 2016)
In this study, the concept of targeted photodynamic therapy, a method to induce cell death, was tested for epithelial ovarian cancer. Therefore, a recombinant single-domain antibody (7D12) was conjugated site-specifically to the photosensitizer IRDye700Dx by sortase-mediated transpeptidation (sortagging) and click chemistry. Cell binding and phototoxicity of these conjugates was evaluated in vitro in three different cell lines with different levels of epidermal growth factor receptor (EGFR)-expression. It was demonstrated that targeting of IRDye700Dx with 7D12 lead to specific binding of these conjugates to high EGFR-expressing cells, allowing cell killing of only these cells after illumination of the photosensitizer.